Who better than you? : the art of healthy arrogance & dreaming big - Packer, Will (Harmony, 2025)
"You know Will Packer's movies. From Straight Outta Compton to Girls Trip, they've grossed more than $1 billion at the box office, including ten films that opened at number one. And, in the vein of Shonda Rhimes, he did it all by featuring real life stories about Black culture-something that Hollywood had long overlooked. With Who Better Than You?, Packer reflects on the values that carried him on his journey: the hustle that fueled him when he was trying to sell a micro-budget indie film in college and the passion and collaboration that led to some of his most successful projects. He has created a guidebook filled with indispensable advice on business, leadership, and legacy. Whether you're aiming for the writer's room or the boardroom, you will find encouragement, energy, and empowerment in his stories and lessons"--